2021
DOI: 10.1111/jopy.12645
|View full text |Cite
|
Sign up to set email alerts
|

Personality traits relate to chronotype at both the phenotypic and genetic level

Abstract: Introduction: Diurnal preferences have been linked to personality but often with mixed results. The present study examines the relationships between sleep timing (chronotype), diurnal preferences and the Five-Factor Model of personality traits at the phenotypic and genetic level. Methods: Self-and informant-reports of the NEO Personality Inventory-3, self-reports of the Munich Chronotype Questionnaire, and DNA samples were available for 2,515 Estonian adults (Mage = 45.76 years; 59% females). Genetic correlati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 129 publications
(165 reference statements)
2
8
0
Order By: Relevance
“…The results provide further evidence that specific aspects of the Big Five personality traits are associated with a diurnal preference. In line with the existing evidence, agreeableness, conscientiousness, and emotional stability were separately related to morningness [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. More crucially, for the first time, we evidenced that the dimensions of Type-D personality and multidimensional perfectionism are associated with a diurnal preference.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…The results provide further evidence that specific aspects of the Big Five personality traits are associated with a diurnal preference. In line with the existing evidence, agreeableness, conscientiousness, and emotional stability were separately related to morningness [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. More crucially, for the first time, we evidenced that the dimensions of Type-D personality and multidimensional perfectionism are associated with a diurnal preference.…”
Section: Discussionsupporting
confidence: 85%
“…However, most studies focus on the five-factor model of personality [ 10 ]. Here, the relationship between morningness and conscientiousness (i.e., a tendency to be reliable, well organized, and hardworking) is perhaps the most reliable to date, consistently observed in student- and general-population samples [ 11 , 12 , 13 , 14 , 15 , 16 , 17 ]. In addition, greater levels of agreeableness (i.e., the tendency to act warm, friendly, and tactful), emotional stability (i.e., reduced experience of emotionally reactive behavior and negative emotions), and openness to experience (tendency to be open-minded, imaginative, and creative) have been differentially reported amongst Polish [ 11 ], Estonian [ 12 ], and Italian [ 17 ] adults, and Polish [ 14 ], German [ 13 ], and Canadian [ 16 ] students.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Limited studies have found personality traits to be associated with circadian preference. Morning type preferences, and those positively associated with restrained eating, have been linked to high scores of conscientiousness [38][39][40][41] and, to some extent, agreeableness [39,42]. On the other hand, evening-type preferences and preferences positively associated with uncontrolled eating behavior and eating later in the day have been linked to high scores of neuroticism [43][44][45].…”
Section: Introductionmentioning
confidence: 99%